Energy-related CO2 emissions growth in ASEAN countries: Trends, drivers and policy implications - Suwin Sandu (2020)
© 2019 by the authors. The primary objective of this paper is to analyse the growth of energy-related CO2 emissions in ASEAN (Association of Southeast Asian Nations), with specific emphasis on identifying its trends and underlying drivers. This objective is premised on the arguments that: (1) there is a general lack of analysis of energy-related CO2 emissions growth across ASEAN countries; and (2) such an analysis is critical, because it could enable an assessment to be made of the efficacy of existing energy policies for reducing emissions. Decomposition analysis is the main approach adopted in this paper. The findings of this paper suggest that the growth of energy-related CO2 emissions has slowed in some major emitters in the region, due to energy efficiency improvement, and, to a lesser extent, a gradual switch in energy fuel mix towards lower emission sources (gas and renewables). However, this improvement is unlikely to drive a major transformation in the energy sectors of the region to the extent considered adequate for redressing the challenge of rising emissions, as indicated by a steady emissions growth in most ASEAN countries over the entire study period (1971–2016). By implication, this suggests that a significant scale-up of existing policy effort is needed to rectify the situations.